Hydrogen bonding phase-transfer catalysis with sodium azide and potassium cyanide - Wang, J (2021)
Hydrogen Bonding-Phase Transfer Catalysis (HB-PTC) enables use of alkali metal fluoride salts as reactive reagents in enantioselective catalysis and this platform has been successfully applied towards enantioselective fluorination. This thesis details a study into the structure and reactivity of hydrogen bonded azide and cyanide anions and the development of enantioselective reactions using sodium azide and potassium cyanide under HB-PTC for the synthesis of enantioenriched organoazide and organonitriles.